Identifikasi Keberadaan Cekungan Air Tanah Ciomas, Bogor, Berdasarkan Hasil Pendugaan Geolistrik - Tatang Padmawidjaja (JURNAL SUMBER DAYA AIR, 2010)
Geoelectric research to estimate soil water basins and aquifers have been conducted in the area Ciomas District, Bogor Regency. The geology in this location including the Bogor Basin and Bogor linemen, with rocks that occupy it is Volcanic of Quaternary rocks of the Formation of Bojongmanik. Formation of Bojongmanik consists of coarse sand to fine clay and calcareous rocks. Resistivity shows the boundary curves at depths greater than 200 meters which indicate the boundary between areas of conductive and resistive. The resistivity has a value smaller than 10 ohm m of sandy clay material as a mineral deposit groundwater. Based on resistivity data is that the area Ciomas is rare soil water aquifer that is trapped in the layers of clay and layers which in impermeable.